2015
DOI: 10.4103/0366-6999.151104
|View full text |Cite
|
Sign up to set email alerts
|

A Time Series Observation of Chinese Children Undergoing Rigid Bronchoscopy for an Inhaled Foreign Body

Abstract: Background:In China, tracheobronchial foreign body (TFB) aspiration, a major cause of emergency episode and accident death in children, remains a challenge for anesthetic management. Here, we share our experience and discuss the anesthetic consideration and management of patients with TFB aspiration.Methods:This was a single-institution retrospective study in children with an inhaled foreign body between 1991 and 2010 that focused on the complications following rigid bronchoscopy (RB). Data including the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…In Zhang et al's retrospective review of patients in their institution who had undergone rigid bronchoscopy for foreign body aspiration between 1991 and 2010, mortality rate was 0. 3%, whereas Boufersaoui et al had a mortality rate of 0.26% . These reports suggest that bronchoscopy is associated with a decreased mortality rate in AFBs when compared to all children with this diagnosis.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In Zhang et al's retrospective review of patients in their institution who had undergone rigid bronchoscopy for foreign body aspiration between 1991 and 2010, mortality rate was 0. 3%, whereas Boufersaoui et al had a mortality rate of 0.26% . These reports suggest that bronchoscopy is associated with a decreased mortality rate in AFBs when compared to all children with this diagnosis.…”
Section: Discussionmentioning
confidence: 89%
“…The percentage of patients with preoperative respiratory symptoms, complications, and negative bronchoscopies increased between 2005 and 2010. They felt that preoperative respiratory symptoms predicted postoperative complications . An Algerian study of children, most of whom had bronchoscopies for an AFB, spanning the years 1989 to 2012, showed a complication rate of 0.29% .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pneumothorax is an uncommon complication of rigid bronchoscopy and previous studies with 3149 cases in the paediatric group showed an incidence of 0.3% [22]. Mechanical trauma to the tracheobronchial tree by the rigid bronchoscope as well as high peak inspiratory pressure during mechanical ventilation are likely causes of pneumothorax.…”
Section: Parametersmentioning
confidence: 95%